Generalized AA amyloidosis and fibrino-hemorrhagic pancreatitis in a Gazelle subgutturosa: a case report - Ceribasi, A. O.; Eroksuz, Y.; Ceribasi, S.; Ozer, H. (Czech Academy Agricultural Sciences, 2009)
Generalized AA Amyloidosis and fibrino-hemorrhagic pancreatitis were diagnosed in a 6-year-old, male Gazelle subgutturosa submitted for necropsy from a Wild Animal Production Station in Malatya, a province from eastern Turkey. Adhesions between the visceral surfaces of abdominal organs including the liver, pancreas, diaphragma and spleen were observed in the necropsy. Microscopically, the mass consisted of fibrino-hemorrhagic pancreatic tissue. Chronic inflammatory reactions characterized by mononuclear cell infiltration and fibrous connective tissue proliferation were found on the serosal surface in the liver. Amyloid depositions were detected and confirmed by Congo red stained sections of the pancreas, liver, kidneys, and spleen viewed under a polarized light microscope. Generalized AA amyloidosis was thought to responsible for a chronic inflammation characterized by adhesions in Gazelle subgutturosa. Generalized AA amyloidosis along with pancreatic involvement and fibrino-hemorrhagic changes are described for the first time in the Gazelle subgutturosa species.
Keywords: AA amyloidosis; Gazelle subgutturosa; gazelle; pancreatitis